A Loftier Flight The Life and Accomplishments of Charles-Louis Didelot, Balletmaster (Wesleyan University Press, 1974)
Charles-Louis Didelot (1767-1837) was a French balletmaster in the fullest sense of the word: an exacting teacher-director, whose many contributions included dancing en pointe and mime work; a highly imaginative choreographer, who often collaborated with his composers and even instructed the orchestra; an innovative scenographer, whose insistence on authenticity and realism in costuming and staging revolutionized the production of ballet. Above all, he was a perfectionist; and in Revolutionary Paris, in Regency London and in Imperial Petersburg Didelot single-mindedly pursued his career, ignoring royal imperatives and fighting court intrigues and theatrical politics to realize as fully as possible his larger vision of the dance. Based upon extensive research in four languages, Mary Grace Swift's book is the first biography in English of Didelot. It is a full, impressively documented account of his life and career, in which she brings vividly to life the artistic milieu in which Didelot flourished.